Change Detection and Image Time Series Analysis 1 2021
DOI: 10.1002/9781119882268.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds and Distances to Better Detect Wet Snow over Mountains with Sentinel‐1 Image Time Series

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This article does not address the impact of reference image selection on wet snow detection. The study in [42] showed that examining the cross-correlations between images calculated over an entire time series allows for a better selection of reference images (with less similarity to the winter period). This approach was tested in [38] to better detect avalanche debris.…”
mentioning
confidence: 99%
“…This article does not address the impact of reference image selection on wet snow detection. The study in [42] showed that examining the cross-correlations between images calculated over an entire time series allows for a better selection of reference images (with less similarity to the winter period). This approach was tested in [38] to better detect avalanche debris.…”
mentioning
confidence: 99%